A Systemic Review of Beta Caryophyllene - Janadri, Suresh; Kumar R, Ranjith; P M, Manjunatha; Sharma, Uday Raj; Vada, Surendra; T, Haribabu; M V, Madhu; Angadi, Preeti P (Defence Life Science Journal, 2024)
A naturally occurring sesquiterpene known as..........